Inventory Control Models in Indian SMEs: An Empirical Assessment Based on Enterprise Classification - Rohit Mohite; Ravi Chaurasiya; Sandeep Sharma (Indonesia Academia Research Society, 2025)
Inventory control remains a cornerstone of operational efficiency in Small and Medium Enterprises (SMEs) in India, yet systematic evaluation across enterprise classifications—micro, small, and medium has been limited. This study empirically investigates the adoption and effectiveness of key inventory control models, including Economic Order Quantity (EOQ), Just-In-Time (JIT), and ABC analysis, in a cross-sectional sample of 450 SMEs across manufacturing clusters in Maharashtra, Tamil Nadu, and Gujarat. Findings indicate that microenterprises prefer heuristic and manual methods, whereas medium enterprises exhibit higher adoption rates of quantitative models such as EOQ and JIT. A chi-square analysis confirmed significant differences in model adoption across enterprise classifications. The study further identifies the primary drivers and inhibitors of model adoption, including digital readiness, training levels, and working capital constraints. The implications are crucial for policymakers and practitioners aiming to tailor inventory interventions to SME sub-types. This research bridges a critical gap in inventory literature by aligning control models with real operational contexts within the SME spectrum in India.